PENGARUH KESIAPAN GURU DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA DAN DUKUNGAN ORANG TUA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL KELAS VIII DI SMP SWASTA TAMAN SISWA PEMATANG SIANTAR - Lena Sapitri Naibaho; Anton Luvi Siahaan; Anggun Tiur Ida Sinaga (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to gain knowledge regarding the influence of teacher readiness in implementing the Merdeka curriculum and parental support on student learning outcomes in class VIII social science subjects at Taman Siswa Pematang Siantar Private Middle School.This type of research is quantitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 21. The population in this study was 76 people, and the sample used was 76 people. The sample collection technique used was a saturated sample. The data collection technique used was a questionnaire. The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2).The results of this research state that: 1) there is a positive influence of teacher readiness on student learning outcomes. This result can be seen in the t test where the t value of teacher readiness (3.270) > t table value (1.993). 2) there is a positive and significant influence of parental support on student learning outcomes. This result can be seen in the t test where the t value of parental support (2.942) > t table value (1.993) which means this variable is significant. 3) parents' income and social style jointly influence financial behavior. This result can be seen in the F test where the Fcount value (8.730) > Ftable value (3.12). The R Square coefficient of determination test was found to be 0.493, which means that 49.3% of the variables of teacher readiness and parental support had an influence on learning outcomes and 86% was the influence of other variables not examined in this research.